ANALISIS HUBUNGAN FAKTOR DOMINAN DENGAN KINERJA KARYAWAN NON MEDIS DI RSU KARYA HUSADA PERDAGANGAN - Silitonga, Rini Santya (Jurnal Inovasi Kesehatan Masyarakat, 2025)
The purpose of this research was to identify the factors that contribute to the positive or negative work environment, employee morale, and productivity among non-medical staff at RSU Karya Husada Perdagangan. Quantitative studies using a cross-sectional design were the norm. The 47 non-medical staff members of RSU Karya Husada Perdagangan made up the study's population. A total of 47 people participated in the survey. We employed the census sampling method for our sample technique. Questionnaires measuring work ethic, work discipline, and satisfaction with work environment and performance served as the main data set, which was subsequently analyzed using the Kendall tau test. The majority of RSU Karya Husada Perdagangan's non-medical staff members shown adequate levels of motivation, self-control, and satisfaction with their working conditions. A substantial association between work enthusiasm, work discipline, and perceptions of work facilities and performance was shown by the results of the Kendall tau correlation test, which yielded a p value of 0.026 <α = 0.05. There was a strong enough association between performance and factors including work excitement, work discipline, and eval_uations of work facilities (r=0.313). The study's authors concluded that non-medical staff at RSU Karya Husada Perdagangan can be more engaged, disciplined, and satisfied with their work and the hospital's facilities if the administration prioritizes their comfort and well-being, treats both current and prospective employees with respect, and fosters a sense of community.